2016
DOI: 10.1103/physrevb.93.165421
|View full text |Cite
|
Sign up to set email alerts
|

Light-hole exciton mixing and dynamics in Mn-doped quantum dots

Abstract: We investigate theoretically the spectral and dynamical effects of the short-range exchange interaction between a single manganese (Mn) atom hosted by cylindrical CdTe quantum dots and its light-hole excitons or biexcitons. Our approach is based on the Kohn-Luttinger k · p theory and configuration interaction method, the dynamics of the system in the presence of intraband relaxation being derived from the von Neumann-Lindblad equation. The complex structure of the light-hole exciton absorption spectrum reveals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the absence of the Mn‐QD exchange interaction, one uses the configuration interaction method to calculate “exchange‐free” exciton and biexciton states false|ν,Mz defined by the equation trueHˆ0false|ν,Mz=Eνfalse|ν,Mz where trueHˆ0=trueHˆKL+trueHˆC+trueHˆcoul+D0trueMˆz2, and the hat denotes the second quantized form of the single‐particle operators. The diagonalization implies all many‐body configurations generated by the highest energy NV single‐particle states in the VB and by the lowest energy NC states in the CB (more details are given in ). trueHˆcoul describes the Coulomb interaction.…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In the absence of the Mn‐QD exchange interaction, one uses the configuration interaction method to calculate “exchange‐free” exciton and biexciton states false|ν,Mz defined by the equation trueHˆ0false|ν,Mz=Eνfalse|ν,Mz where trueHˆ0=trueHˆKL+trueHˆC+trueHˆcoul+D0trueMˆz2, and the hat denotes the second quantized form of the single‐particle operators. The diagonalization implies all many‐body configurations generated by the highest energy NV single‐particle states in the VB and by the lowest energy NC states in the CB (more details are given in ). trueHˆcoul describes the Coulomb interaction.…”
Section: The Modelmentioning
confidence: 99%
“…We shall denote by Pν,Mz:=ν,Mzfalse|ρˆfalse(tfalse)false|ν,Mz the population of the state false|ν,Mz. Fore more details we refer to .…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For all the systems studied so far it has been found that the ground state of the magnetic ion is significantly influenced by the local strain present in a quantum dot. Such an effect is of particular importance for future applications in solotronics (optoelectronics based on single dopants [17]) and spintronics based on magnetic QDs [18][19][20][21][22][23][24][25][26][27][28]. The effect of strain may be demonstrated as beating in the coherent precession of the single magnetic ion spin [29], as changes of occupation and energy of levels corresponding to various projections of the ion spin [1,7,15], or even as a change in the character of the Fe 2+ ion ground state, from nonmagnetic in bulk to magnetic in a QD [13].…”
Section: Introductionmentioning
confidence: 99%